Directional light beams by design from electrically driven elliptical slit antennas - Cao, Shuiyan; Le Moal, Eric; Jiang, Quanbo; Drezet, Aurélien; Huant, Serge; Hugonin, Jean-Paul; Dujardin, Gérald; Boer-Duchemin, Elizabeth (Beilstein Journal of Nanotechnology, 2018)
We report on the low-energy, electrical generation of light beams in specific directions from planar elliptical microstructures. The emission direction of the beam is determined by the microstructure eccentricity. A very simple, broadband, optical antenna design is used, which consists of a single elliptical slit etched into a gold film. The light beam source is driven by an electrical nanosource of surface plasmon polaritons (SPP) that is located at one focus of the ellipse. In this study, SPPs are generated through inelastic electron tunneling between a gold surface and the tip of a scanning tunneling microscope.
Keywords: elliptical antenna; inelastic electron tunneling; optical antenna; plasmonics; scanning tunneling microscopy; surface plasmon polariton